Predicting Difficult Airway Intubation Based on Maxillofacial Trauma: A Retrospective Study - Yang, James; Trivedi, Aakash; Alvarez, Zoraida; Bhattacharyya, Ratul; Sartorato, Felippe; Gargano, Francesco; Rebein, Benjamin; Zuberi, Jamshed (Curēus (Palo Alto, CA), 2022)
Purpose The purpose of this study was to determine which types of facial injuries in traumatic patients' wounds cause difficult intubation for anesthesiology team. By anticipating potential complications with airway management, the surgeons can be better prepared for emergent cricothyrotomy if needed. This could include prior to the planned procedure in the operating room (OR) as well as in emergent conditions in trauma bay. Methods Trauma patients with facial injuries in a level II trauma center from January 2007 to September 2017 that required intubation were evaluated for types of facial injury. Anesthesiology intubation documents were reviewed to determine which types of facial injuries were associated with difficult intubation per anesthesiology documentation. Results A total of 232 subjects were selected and it was found that patients with LeFort II facial fracture, bilateral mandibular fracture, and facial fracture associated with basilar skull fracture were noted to have difficult intubation by the anesthesiology team. Conclusion On the basis of CT imaging findings, our study demonstrates that certain types of facial fractures could pose difficult intubation. Surgeons should be aware of these injuries and be ready to intervene with emergent cricothyrotomy if necessary.